1999
DOI: 10.1089/thy.1999.9.1037
|View full text |Cite
|
Sign up to set email alerts
|

Successful Outcome of Pregnancy in a Thyroidectomized-Parathyroidectomized Young Woman Affected by Severe Hypothyroidism

Abstract: Severe hypothyroidism was discovered in a young woman in her 29th week of pregnancy. Previously, at the age of 12 years, she had undergone thyroid surgery for Graves' disease that resulted in persistent hypothyroidism and hypoparathyroidism. After surgical excision, the patient started levothyroxine replacement therapy and had regular control of thyroid function with normal findings throughout the years. The dose of levothyroxine had not been adjusted when the pregnancy started, and at the 29th week of gestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, lack of statistical significance may be at least in part dependent upon the small sample size of our study group as well as the different prevalence of thyroidectomized vs Hashimoto's-affected patients (27.3% and 57.1%) in groups I and II respectively. Such results should not encourage delaying the first post-conception hormone evaluation; this should always be performed as soon as possible since previous studies have demonstrated that even patients under a suppressive L-T4 regimen before pregnancy may turn severely hypothyroid in later stages of gestation (22,23). In other words, women under partially suppressive therapy, even when euthyroid at the first post-conception hormonal evaluation, must be re-evaluated in later stages of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…However, lack of statistical significance may be at least in part dependent upon the small sample size of our study group as well as the different prevalence of thyroidectomized vs Hashimoto's-affected patients (27.3% and 57.1%) in groups I and II respectively. Such results should not encourage delaying the first post-conception hormone evaluation; this should always be performed as soon as possible since previous studies have demonstrated that even patients under a suppressive L-T4 regimen before pregnancy may turn severely hypothyroid in later stages of gestation (22,23). In other words, women under partially suppressive therapy, even when euthyroid at the first post-conception hormonal evaluation, must be re-evaluated in later stages of pregnancy.…”
Section: Discussionmentioning
confidence: 99%